(Micro)spectroscopy investigations of the properties of soft colloidal particles and perovskite materials - Wang, Jin (2018)
The crystallization of soft colloidal particles, properties of perovskite quantum dots and interaction between perovskite microrods and upconversion nanoparticels are investigated by microscopy. Single particle tracking is investigated via wide field microscope to analyze the fluid-to-crystal phase transition. By mean square displacement analysis, two types of motions prior to crystal state and the influence induced by pH have first been analyzed. Perovskite quantum dots (PK QDs) of FAxMA1-xPbX3 alloy were successfully prepared via a facile ligand-assisted reprecipitation recipe at room temperature. The as-synthesized PK QDs have high quantum efficiencies peaking at 84%, which could even rise to 96% in 12h resting time. Furthermore, we have synthesized FA0.24MA0.76PbI3 perovskite microrods in a two-step solution based method. The photoluminescence and lifetime trajectories were recorded to investigate the interaction between perovskite and upconversion materials.